2009
DOI: 10.1590/s0103-84782009005000160
|View full text |Cite
|
Sign up to set email alerts
|

Infecção por Hepatozoon canis em canino doméstico na região Sul do Brasil confirmada por técnicas moleculares

Abstract: Infecção por

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 18 publications
1
8
0
2
Order By: Relevance
“…However, studies by Gondim et al (1998) and Mundim et al (2008) reported anemia as the most frequent hematological alteration. In contrast, studies by O' Dwyer et al (2006) and Lasta et al (2009) did not detected significant hematological and biochemical alterations in dogs evaluated from Botucatu and Porto Alegre, respectively, which was similar to that observed in the present study. According to O'Dwyer (2011), hematological abnormalities, even if having significant association with H. canis infection can be related to coinfection with other blood parasites.…”
Section: Discussionsupporting
confidence: 87%
“…However, studies by Gondim et al (1998) and Mundim et al (2008) reported anemia as the most frequent hematological alteration. In contrast, studies by O' Dwyer et al (2006) and Lasta et al (2009) did not detected significant hematological and biochemical alterations in dogs evaluated from Botucatu and Porto Alegre, respectively, which was similar to that observed in the present study. According to O'Dwyer (2011), hematological abnormalities, even if having significant association with H. canis infection can be related to coinfection with other blood parasites.…”
Section: Discussionsupporting
confidence: 87%
“…gamonts were observed in the peripheral blood of a dog, and the sequence confirmed that homology with H. canis existed. This was the first molecular detection of H. canis in southern Brazil (LASTA et al, 2009).…”
Section: Epidemiologymentioning
confidence: 89%
“…A molecular survey was conducted among dogs in Grenada, in the Caribbean, and 7% were positive for H. canis (YABSLEY et al, 2008 (MUNDIM et al, 1992(MUNDIM et al, , 1994(MUNDIM et al, , 2008a, Rio de Janeiro (MASSARD, 1979;O'DWYER et al, 2001;SÁ et al, 2007), Rio Grande do Sul (MASSARD, 1979;LASTA et al, 2009), São Paulo (GONDIM et al, 1998RUBINI et al, 2005;O'DWYER et al, 2006) and, most recently, Pernambuco (DANTAS-TORRES et al, 2010;RAMOS et al, 2010). This infection has also been detected in domestic cats: in São Paulo (PEREZ et al, 2004), with molecular characterization demonstrating high similarity with H. canis (RUBINI et al, 2006); and in Maranhão, with Hepatozoon DNA showing more similarity with H. felis (DE BORTOLI et al, 2011).…”
Section: Epidemiologymentioning
confidence: 99%
“…No Brasil, a hepatozoonose canina já foi relatada na região Sudeste (O'DWYER et al, 2001;MUNDIM et al, 2008a;SPOLIDORIO et al, 2009), Centro-Oeste (MUNDIM et al, 2008bPALUDO et al, 2003;RAMOS et al, 2015) e Sul (LASTA et al, 2009). No Nordeste brasileiro, a prevalência da doença foi estudada apenas no Recife, estado de Pernambuco, por Ramos et al (2010) e, recentemente, por Rotondano et al (2015) …”
Section: O Cão Se Infecta Ao Ingerir Carrapatos Contendo Oocistos Madunclassified